Profile of patients seen in consultation-liaison psychiatry in a multidisciplinary hospital - Poudel, Lata Gautam; Poudel, Samir Kumar (Journal of Psychiatrists' Association of Nepal, 2024)
Introduction: Consultation liaison (C-L) psychiatry is a bridge that interlinks psychiatry with the other branches of medicine. Timely identification of mental disorders and their management in medically ill patients hastens the recovery process, shortens hospital stay, minimizes undue economic burden to the patients, improves patients’ co-operation and strengthens doctor- patient therapeutic relationship. Therefore C- L psychiatry has important role in holistic patient management in every hospital setting. Materials and Methods: This is a hospital-based retrospective study done in National Academy of Medical Sciences, Bir Hospital, Kathmandu. A total of 420 patients were examined by the consultants in different non-psychiatry wards and recorded manually were enrolled in the study. This study was conducted to find out the burden of mental disorders in patients admitted for non-psychiatry causes in different wards. Study duration was one year. Results: Out of 420 patients enrolled in the study, 60.71% were males and the mean age of the population was 44.29 +16.49 years. Age range was 14 years to 90 years. Most of the patients were referred from the medical ward, orthopedic ward and medical ICU. The first three mental illnesses in the study were alcohol dependence syndrome (22.1%), delirium due to medical causes (15.5%) and depressive disorders (14%). 11.90% of the total cases had presented with suicide attempt. Among those who attempted suicide, impulsive act and underlying depression were most observed. Conclusion: C-L Psychiatry has a crucial role in diagnosing mental illnesses in patients admitted to non-psychiatry wards so that the holistic approach to the care of patients can be instituted. Addressing the issues from psychiatric aspect improves the outcome of the patients leading to shorter hospital stay and better recovery. Most common mental disorders in C-L Psychiatry in our settings were alcohol dependence syndrome, delirium due to medical causes and depressive disorders respectively.